Dynamic temporal signal processing in the inferior colliculus of echolocating bats - Jen, Philip; Wu, Chung H.; Wang, Xin (Frontiers in Neural Circuits, 2012)
In nature, communication sounds among animal species including humans are typical complex sounds that occur in sequence and vary with time in several parameters including amplitude, frequency, duration as well as separation and order of individual sounds. Among these multiple parameters, sound duration is a simple but important one that contributes to the distinct spectral and temporal attributes of individual biological sounds. Likewise, the separation of individual sounds is an important temporal attribute that determines an animal’s ability in distinguishing individual sounds. Whereas duration selectivity of auditory neurons underlies an animal’s ability in recognition of sound duration, the recovery cycle of auditory neurons determines a neuron’s ability in responding to closely spaced sound pulses and therefore it underlies the animal’s ability in analyzing the order of individual sounds. Since the multiple parameters of naturally occurring communication sounds vary with time, the analysis of a specific sound parameter by an animal would be inevitably affected by other co-varying sound parameters. This is particularly obvious in insectivorous bats which rely on analysis of returning echoes for prey capture when they systematically vary the multiple pulse parameters throughout a target approach sequence. In this review article, we present our studies of dynamic variation of duration selectivity and recovery cycle of neurons in the central nucleus of the inferior colliculus of the frequency-modulated bats to highlight the dynamic temporal signal processing of central auditory neurons. These studies use single pulses and three biologically relevant pulse-echo (P-E) pairs with varied duration, gap and amplitude difference similar to that occurring during search, approach and terminal phases of hunting by bats. These studies show that most collicular neurons respond maximally to a best tuned sound duration (BD). The sound to which these neurons are tuned correspond